PEROLEHAN TANAH DALAM PENGADAAN TANAH BERSKALA KECIL - Urip Santoso Urip Santoso (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2011)
Abstract: Government is a side or party that needs land in terms of trivial scale of land provision. The way of land acquisition in trivial scale must pass through the way of referential settlement release by the land owner. It is not allowed to have it by purcahsing and saling and also exchanging. The later way of land acquisition cannot be done due tp in adequacy of term of material of purcahsing and saling as well as exchanging. Key Words: Pengadaan tanah, berskala kecil, jual beli, tukar-menukar, dan pelepasan hak atas tanah.